Condições de acesso e permanência das mulheres no movimento sindical - Santos, Verônica de Barros (2018)
This study is an analysis of the conditions of access and permanence of women in the trade union movement. The issue is framed in the discussions on the political participation of women and the cut is the trade union movement. Considering that the political and trade union fields have traditionally been dominated by men, and considering the increasing participation of women, we aim to investigate the constraints of their insertion in these spaces. To that end, we selected as a reality to be observed the category of Technical-Administrative in Education - TAE, formed by professionals that make up the administrative sphere of Brazilian public higher education institutions. The representation tables, previously composed predominantly by men, gradually changed with the presence of women. Because of these changes, we propose to think the mechanisms that justify them and frame the analysis from two perspectives. In the first, we place the category of TAE in front of the institution that represents it nationally, the Federation of Trade Unions of Technical-Administrative Workers in Public Higher Education Institutions of Brazil - FASUBRA Sindical. In this regard, we analyze the composition of the national leadership and the directorates/coordinations of the affiliated unions, taking into account the percentages and places occupied by men and women. In the second, we selected one of the affiliated unions, the Syndicate of Technical-Administrative Workers in Education of the Federal University of Sergipe - SINTUFS. We seek to understand the conditions of access and permanence of women with the focus on the relational aspects around the engagement of the militants. The study was guided by the sociology of militancy and the gender approach, and the main concepts and notions employed were: trajectories, careers, sexual division of labor, militant engagement and social bonds. We use different methodological strategies, such as document consultation, questionnaire application, participant observation and biographical interview. We have identified the presence of many women in the directorates/coordinations of FASUBRA's basic institutions. However, differences were also observed in the number of places occupied by men and women. The social ties and some experiences found in women's itineraries have emerged as a mechanism to explain their entry and stay in union leadership. Among the types of links, the personalities were more relevant, and educational experiences were the most significant resources for engagement. We find that, in general, the increase of women in the trade union movement is associated with their participation in the labor market and the cultural and social transformations that affect the role of women in society. The unionists justified that the awareness of the need to occupy political spaces by women and, especially, the commitment to the working class were the reasons for their militant engagement.